Repetitive Artery-to-Artery Embolism Caused by Dynamic Movement of the Internal Carotid Artery and Mechanical Stimulation by the Hyoid Bone. Issue 3 (21st July 2015) - Tokunaga, Keisuke; Uehara, Toshiyuki; Kanamaru, Hideki; Kataoka, Hiroharu; Saito, Kozue; Ishibashi-Ueda, Hatsue; Shobatake, Ryogo; Yamamoto, Yoshifumi; Toyoda, Kazunori
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.